(untitled) (Journal of Current and Advance Medical Research, 2014)
Emergence of bacterial resistance causes limitation of the action of antimicrobial agents. Frequency of extended spectrum ?-Lactamase (ESBL) production is high among Escherichia coli (E. coli) and Klebsiella species. This has created a worldwide problem resulting in treatment failure. ESBLs have become widespread throughout the world. Microbes undergo mutation of genes, which can spread from cell to cell by mobile genetic elements such as plasmids, transposons and bacteriophages. Resistant bacteria flourish in areas of heavy antibiotic use such as hospitals and ICU. With widespread use of antibiotic, the frequency of penicillinase producing staphylococci increased. The availability of the second-generation cephalosporin, such as cefamondole, cefoxitin, and cefuroxime, or 3rd generation cephalosporin, such as cefotaxime, ceftazidime, ceftriaxone has been the leading cause of potential resistances in nosocomial Gram-negative bacilli. Hospital outbreaks of multi-drug resistant Enterobacteriaceae are now being frequently caused by extended spectrum beta-lactamase (ESBL) producers. Incidence of ESBL producing strains among clinical isolates has been steadily increasing over past years resulting in limitation of therapeutic options. Bacterial antibiotic resistance has become a major clinical concern worldwide including Bangladesh. Recently, the use of second and third generation cephalosporin has led to the selection of Gram-negative organisms resistant to ?-lactamase stable cephalosporin. This resistance is attributed to the production of extended spectrum ?-lactamases. DOI: http://dx.doi.org/10.3329/jcamr.v1i1.19560 J Curr Adv Med Res 2014;1(1):13-19